Silencing Effect: Analisis Kekerasan Verbal Berbasis Gender Online terhadap Partisipasi Politik Perempuan di Platform TikTok - Minerva Laisa Sabatini; Azalia Salsabila; Ika Arinia Indriyany (Journal of Research and Development on Public Policy, 2026)
The expansion of digital technology, particularly social media platforms, has created broader opportunities for public engagement in political discussions, including for women. Digital platforms allow women to share political perspectives, contribute to public opinion, and participate in political conversations that have traditionally been dominated by formal political actors. Nevertheless, the growing involvement of women in digital political spaces has also been accompanied by an increase in online gender-based violence (OGBV). This study aims to identify the forms of OGBV and examine its impact on women’s political participation on social media. The research adopts a qualitative approach using discourse analysis to analyze public comments responding to political content posted by the influencer Satya Salsabila on TikTok. The findings indicate that women who express political opinions online frequently encounter personal attacks such as verbal harassment, sexually suggestive remarks, body shaming, and attempts to question or undermine women’s credibility in discussing political matters. These acts of harassment not only function as symbolic violence against individuals but also reflect persistent gender stereotypes and patriarchal power relations that continue to shape interactions within digital environments. Such experiences may influence women’s sense of security and confidence when expressing political viewpoints online, potentially limiting their participation in digital political discussions. Therefore, creating safer, more inclusive, and equitable digital spaces is essential to support women’s active participation in political discourse.